Practical aspects of WTO litigation - Tejeda, Marco Tulio Molina (Global trade law series ;, 2020)
"This book provides the first in-depth practical guide to resolving a dispute at the WTO, edited by an international lawyer, who has on-hands experience in WTO litigation."